Novel Energy-Centric Analysis for Random Access Networks - Dester, Plinio S. [UNESP]; Costa, Maice; Nardelli, Pedro H. J.; Goria Silva, Pedro E.; Moualeu, Jules M. (Institute of Electrical and Electronics Engineers (IEEE), 2025)
In this letter, we revisit the notion of energy efficiency widely adopted in age-centric network-based systems. To this end, we consider two traditional ALOHA random-access protocols (unslotted ALOHA and slotted ALOHA) wherein their total energy consumption is analyzed. The importance of considering the total energy needed to deliver timely information stems from the increasing data consumption through resource-constrained devices, such as sensors in an application of the Internet of Things (IoT). We propose a novel perspective on the energy consumption, taking into account synchronization costs for a fair comparison between the access schemes.
Keywords: Age of information; energy dissipation; packet generation; random access protocols; Energy; Energy-consumption; Network based systems; Packet generations; Random access networks; Random access protocol; Resourceconstrained devices; Synchronization cost; Total energy